HUBUNGAN PERSEPSI BEBAN KERJA DENGAN KINERJA PEGAWAI DI UPT PUSKESMAS MENGANTI GRESIK - Nurul Fitriyatul Azizah; Ima Nadatien; Abdul Hakim Zakkiy Fasya (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACT Background of Study: The problem of decreasing HR performance in an organization must be considered. Many factors affect performance, one of which is the perception of workload. The purpose of this study is to analyze the relationship between perceived workload and employee performance in Public Health Center Menganti Gresik.  Methods:  This research method was descriptive quantitative with a cross sectional approach. The population in this study were all 20 paramedics with civil servant status and were taken using a saturated sampling technique. The variables in this study were perceptions of workload and performance. The instrument used an online questionnaire sheet (google form). Data analysis used contingency coefficient values. Results: The results showed that most (60%) respondents had a positive workload perception and most (65%) respondents had good performance. The results of the contingency coefficient value showed that there was a relationship between perceived workload and performance (0,565), there was a relationship between perceived workload and performance aspects, namely cognitive aspects (0,155) and affective aspects (0,615). From the two aspects, the most related to performance were the affective aspect.  Conclusion: The conclusion in this study is that there was a relationship between perceived workload and performance. Keywords: Workload, Performance, Perception